Penerapan Media Power Point Interaktif Berbasis Animasi dalam Meningkatkan Motivasi Belajar Bahasa Arab Siswa Kelas VII E MTs Islam Al-Mukmin Sukoharjo Tahun Ajaran 2023–2024 - Aisyah Muiz Khayati; Anis Budiriyanto (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2023)
The teaching and learning process engages students when they have interest and enthusiasm for the material or subject being presented, especially when the teacher delivers the material in an engaging way, sparking student curiosity. One way to make learning more engaging is by using learning media. The objectives of this study are: To examine the application of animation-based interactive PowerPoint media in Arabic language subjects. To assess students’ motivation for learning Arabic. To analyze the influence of using animation-based interactive PowerPoint media on improving students’ motivation to learn Arabic. The research method used is a quantitative approach. Based on the research results, the use of animation-based interactive PowerPoint media falls into the moderate category at 66.9%. Student motivation in Arabic language learning is also in the moderate category at 64.2%. The statistical analysis shows tₕᵢₜᵤₙg = 6.519 and tₜₐbₗₑ = 0.128 with df = 31 at a significance level of 1% (0.01). Since tₕᵢₜᵤₙg > tₜₐbₗₑ, the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected. Therefore, it can be concluded that there is a significant influence of applying animation-based interactive PowerPoint media on improving students’ motivation to learn Arabic at MTs Islam Al Mukmin Sukoharjo.